Fazer Territó-rios na Amazônia - Martine Droulers (Confins)
"Territoriver" refers to a territorial construction resulting from the adjustments and interrelations formed by the successive historical and economic periods which have placed the river systems at the center of territorial organizations increasingly meshed.The Amazon basin provides emblematic examples of "Territorivers" derived from the progressive control of rivers since the phases of their exploration, their occupation and finally their regional integration in a highly transformed Amazon